Pengaruh Subtitusi Pasir Pada Tanah Organik Terhadap Kuat Tekan dan Kuat Geser - Putra, Rizki Dwi; Iswan, Iswan; Afriani, Lusmeilia (Universitas Lampung, 2016)
Physical properties of organic soils have a very high water content and low carrying capacity.One method to increase the carrying capacity of the soil is by adding or mixing with materials thathave a high carrying capacity. By adding sand on the sample in this study is expected to increasethe carrying capacity of organic soils of compressive strength and strong shear. The study wasconducted in the laboratory of Soil Mechanics Faculty of Engineering, University of Lampung, bymaking a sample of the results of compaction standard, then the samples are given the addition ofsand to the percentage increments of 5%, 10%, 15%, and 20% for the comparison of thecompressive strength (qu), shear angle (φ), and the value of cohesion (c) after the addition ofsand.Results of testing the compressive strength and shear strength showed soil behavior in a state ofthe sample with the addition of sand up to 20% has an increased qu and φ, but a decline in thevalue of soil cohesion. The more increasing mix of sand in the soil samples, the values ofcohesion / coherence on the ground will be more decreased, but the sand has good gradation andstrong grain will be able to withstand the load that works vertically or horizontally.Keywords: Organic Soil, Compressive strength and Shear strength, Friction Angle, and Cohesion.